Development of polyurethane acrylate coated salt hydrate/diatomite form-stable phase change material with enhanced thermal stability for building energy storage. (30th October 2020) - Xie, Ning; Niu, Junyi; Zhong, Yi; Gao, Xuenong; Zhang, Zhengguo; Fang, Yutang
Highlights: Novel Na2 HPO4 ·12H2 O-Na2 CO3 ·10H2 O/diatomite CPCM is fabricated. Leakage problem are inhibited by a polymer layer coating on the CPCM surface. Supercooling degree has been largely lowered through the composite. The coated CPCM panels could effectively reduce indoor temperature fluctuation. Abstract: Integrating salt hydrate phase change materials (PCMs) into building envelope is a prospective method for retarding indoor temperature fluctuation and thus achieving building energy saving. However, salt hydrates suffer from leakage problem during phase transition, especially dehydration due to their hydrous structure. This paper proposes a two-step stabilizing method is proposed to prepare Na2 HPO4 ·12H2 O-Na2 CO3 ·10H2 O eutectic salt composite PCMs without leakage. The eutectic salt is first combined with porous diatomite and then coated with a layer of ultraviolet (UV)-cured polyurethane acrylate (PUA) to intensify its form stability. Scanning electron microscope (SEM) and leakage tests demonstrated that dehydration problem of inner salt hydrate was successfully inhibited. Besides, a high latent heat of 102.6 J·g −1 and an ignorable supercooling temperature of 0.5 °C were also found. High thermal reliability and stability were demonstrated by thermogravimetric analysis (TGA) and a thermal cycle test. Furthermore, it is shown that when PUA-coated PCM panels were employed as wallboards of a test chamber, the indoor peak temperature and temperature fluctuations could apparently be decreased. All results show that this CPCM exhibits a promising future as an energy source for practical construction fields.